Art Music by Caribbean Composers: Grenada - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2013)
Calypso is “the dominant popular music genre in the country” (Bugros-McLean, 2005, para. 6). At the annual Carnival, bands parade in a festive display of dance, costume, and music – steel pan in particular. “European dances lost in Europe survive in Carriacou” (McDaniel, 1998, p. 868). The music and movements of the quadrille on Carriacou have adapted “indigenous meaning and stylistic reinterpretation” (p. 871). The island of Carriacou also continues to enjoy the traditional “string band music that had been an integral part of the local culture during the Christmas season” (Bugros-McLean, 2005, para. 10).